A time for sex: circadian regulation of mammalian sexual and reproductive function - Sydney Aten; Oscar Ramirez-Plascencia; Chiara Blake; Chiara Blake; Gabriel Holder; Gabriel Holder; Emma Fishbein; Emma Fishbein; Adam Vieth; Adam Vieth; Arman Zarghani-Shiraz; Arman Zarghani-Shiraz; et al. (Frontiers in Neuroscience, 2025)
The circadian clock regulates physiological and biochemical processes in nearly every species. Sexual and reproductive behaviors are two processes controlled by the circadian timing system. Evidence supporting the importance of proper clock function on fertility comes from several lines of work demonstrating that misalignment of biological rhythms or disrupted function of the body’s master clock, such as occurs from repeated shift work or chronic jet lag, negatively impacts reproduction by interfering with both male and female fertility. Along these lines, dysregulation of clock genes leads to impairments in fertility within mammals, and disruption of circadian clock timing negatively impacts sex hormone levels and semen quality in males, and it leads to ovulatory deficiencies in females. Here, we review the current understanding of the circadian modulation of both male and female reproductive hormones—from animal models to humans. Further, we discuss neural circuits within the hypothalamus that may regulate circadian changes in mammalian sexual behavior and reproduction, and we explore how knowledge of such circuits in animal models may help to improve human sexual function, fertility, and reproduction.